2012
DOI: 10.1292/jvms.12-0045
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Profiles of Glucose, Insulin and Lipids in the Male WBN/Kob-<i>Lepr<sup>fa</sup></i> Rat, a New Model of Type 2 Diabetes with Obesity

Abstract: ABSTRACT. Plasma profiles of glucose, insulin and lipids were examined in the male WBN/Kob-Lepr fa (fa/fa) rat, a new model of type 2 diabetes (T2D), in comparison with age-matched original male WBN/Kob (lean) rats. The fa/fa rats developed hypertriglycemia, obesity and hyperglycemia from 5, 7, and 9 weeks of age, respectively. Plasma insulin levels in fa/fa rats were significantly higher than those in lean rats at 5 weeks of age, but after 11 weeks of age gradually declined to the levels in lean rats. HOMA-IR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 18 publications
6
19
0
Order By: Relevance
“…WBKDF-STD rats have been reported to spontaneously develop hyperglycemia and pancreatitis associated with gradual reduction of plasma insulin levels [11, 15, 16]. The present study demonstrated that HFD loading aggravated hyperglycemia in WBKDF rats, which is consistent with the notion that consumption of HFD has a negative influence on the incidence of T2DM [8].…”
supporting
confidence: 89%
See 1 more Smart Citation
“…WBKDF-STD rats have been reported to spontaneously develop hyperglycemia and pancreatitis associated with gradual reduction of plasma insulin levels [11, 15, 16]. The present study demonstrated that HFD loading aggravated hyperglycemia in WBKDF rats, which is consistent with the notion that consumption of HFD has a negative influence on the incidence of T2DM [8].…”
supporting
confidence: 89%
“…The leptin receptor fatty gene ( Lepr fa ) is a recessive mutation that leads to leptin receptor deficiency, and homozygous animals ( fa/fa ) exhibit obesity and hyperphagia, in addition to insulin resistance and glucose intolerance [6]. Previous reports demonstrated that WBKDF rats have severe obesity and insulin resistance, both of which lead to developing T2DM [1, 11, 15, 16]. …”
mentioning
confidence: 99%
“…In a previous study, we demonstrated the involvement of impaired insulin secretion in the development of hyperglycemia in fa/fa rats [7]. The aim of the present study was to examine the role of insulin resistance in the pathogenesis and development of T2DM in fa/fa rats.…”
mentioning
confidence: 83%
“…However, little is known about the relationship between visceral obesity and blood coagulation. This study investigated this relationship by measuring blood coagulation times in 2 distinct visceral obesity models; the WBN/Kob-Lepr fa (fa/ fa) rat, a genetically obese model [2,7], and the C57BL/6J mouse fed a high-fat diet, a DIO model [16]. In both animal models after body weight had plateaued, blood coagulation times were compared with those of age-matched Wistar rats and lean mice fed a standard diet, respectively.…”
mentioning
confidence: 99%